The City as a Multicultural Project: The Case of the City of Lviv (Ukraine) - SVITLANA LINDA (ARCHive-SR, 2025)
There are few monocultural cities, especially in areas that have always been in the crosshairs of global geopolitical change. New political realities have sometimes completely changed the ethnic composition of the city, but the memory of the former inhabitants remains alive in the planning, architecture of buildings, and monuments.